Analisis Keputusan Pembelian Berbasis Sikap Konsumen - Mar’atush Sholihah; Ambar Lukitaningsih; Henny Welsa (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2020)
This study to determine the significance of the positive influence of research variables. The variables of this study are ease of access, attractiveness of post massage, responsiveness of service, consumer attitudes and purchasing decisions. The population of this research is Azza Wedding wedding package consumers in 2019. The number of samples in this study 100 respondents were determined using the Slovin method for known population numbers, data collection methods using probability methods and sampling techniques using simple random sampling. The data analysis tool uses a questionnaire. For testing instruments using the SPSS 18.0 program with a significance level of 0.05. Data analysis techniques for indicator testing, model fit testing and hypothesis testing using the Smart PLS 3.0 program The results of this study indicate: 1) ease of access has a positive and significant effect on consumer attitudes, 2) attractiveness of post massage has a positive and significant effect on consumer attitudes, 3) service responsiveness has a positive and not significant effect on consumer attitudes, 4) consumer attitudes have a positive effect and significant on purchasing decisions, 5) ease of access has a positive and significant effect on purchasing decisions, 6) attractiveness of post massage has a positive and not significant effect on purchasing decisions, 7) responsiveness of service has a positive and not significant effect on purchasing decisions, 8) ease of access positive and significant effect on purchasing decisions through consumer attitudes, 9) attractiveness of post massage has a positive and significant effect on purchasing decisions through consumer attitudes, 10) responsiveness of service has a positive and not significant effect on purchasing decisions through attitude consumer.